2021
DOI: 10.1002/ca.23737
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of the azygos lobe: A meta‐analysis of 1,033,083 subjects

Abstract: The azygos lobe (AL) is an accessory lobe of the right lung with prevalence between 0.4 and 1.2%. The aim of the present review is to provide a better estimate of the frequency of the AL and to examine its relationships with other variables such as population, diagnostic methods, and co-occurring illnesses. Studies published between 1899 and October 2020 were searched through three electronic databases; Google Scholar, PubMed, and JSTOR. Titles, abstracts, and full texts of the retrieved entries were screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 63 publications
(47 reference statements)
1
15
0
3
Order By: Relevance
“…In this study, we took advantage of an open‐access COVID‐19 CT dataset to study the prevalences of six well‐known thoracic anatomical variants in the thorax. We found that the AL was present in 0.8% of COVID‐19 patients, more than twice the global prevalence (Yurasakpong et al, 2021 ). However, this finding alone is not sufficient to demonstrate that individuals with an AL are more predisposed to COVID‐19 infection than others; the finding could be due to the use of different imaging modalities.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In this study, we took advantage of an open‐access COVID‐19 CT dataset to study the prevalences of six well‐known thoracic anatomical variants in the thorax. We found that the AL was present in 0.8% of COVID‐19 patients, more than twice the global prevalence (Yurasakpong et al, 2021 ). However, this finding alone is not sufficient to demonstrate that individuals with an AL are more predisposed to COVID‐19 infection than others; the finding could be due to the use of different imaging modalities.…”
Section: Discussionmentioning
confidence: 64%
“…However, this finding alone is not sufficient to demonstrate that individuals with an AL are more predisposed to COVID‐19 infection than others; the finding could be due to the use of different imaging modalities. In our previous work, we found that most studies used X‐ray to diagnose an AL, and the prevalence of AL obtained from X‐ray studies (2.6%) was significantly lower than that from CT studies (6.7%) (Yurasakpong et al, 2021 ), suggesting that radiographs are less sensitive in detecting the AL. The TB was present in only two patients, a prevalence of 0.2%, which is five times less common than the global average of 1.0% (Wong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 90%
“…In this article, we introduced the CATAM rubric and used it to critically appraise a recently published anatomical MA (Kacprzyk et al, 2020). There have been other anatomical MAs recently published (Aldabe et al, 2019; Bellier et al, 2020; Berthaume & Bull, 2021; Cheruiyot et al, 2021; Dreher et al, 2018; Graves et al, 2017; Harvie et al, 2019; Koziej et al, 2020; Morelli et al, 2019; Nallikuzhy et al, 2018; Roberts et al, 2021; Sirico et al, 2019; Solewski et al, 2021; Stefura et al, 2018; Tomaszewska et al, 2018; Tomaszewska et al, 2018; Tomaszewski et al, 2017; Tomaszewski et al, 2017; Vikse et al, 2016a, 2016b; Whitley et al, 2020; Yammine, 2013, 2014b, 2014c, 2014d; Yammine et al, 2015; Yurasakpong et al, 2021). We believe that the running paper that we used is an exemplary anatomical MA (Kacprzyk et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Including the sample size allows the reader to quickly compare sample sizes between different MAs of the same topic (if previous ones have been published). For two recent examples of anatomical MAs that reported their sample sizes in the titles, see the papers by Kacprzyk et al (2020) and Yurasakpong et al (2021). The running paper title meets our aforementioned criteria because it states that it is a MA and also describes the purpose of the study, which is to analyze the “variations and morphometric features” of the vermiform appendix (Kacprzyk et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study [20] documented a very high prevalence of the stellate type at 25%, although it is worth noting that only 24 skulls were investigated. Overestimation caused by small sample size is known as the small-study effect [21], which reiterates that appropriate sample size is crucial when performing anatomical studies. Another factor which leads to higher heterogeneity between studies is inter-observer variability.…”
Section: Discussionmentioning
confidence: 99%